Política de atención integral en salud (PAIS), “hacia mejores condiciones de la salud” en Colombia (2020)
Health, as an objective (WHO, 1983) and social fact, includes timely, acceptable and affordable access to care of sufficient quality (WHO, 2017). In Colombia, political action for health in recent years has focused on the demand and justice in the face of this as a fundamental right, making necessary critical discussions, of the content and what it is based on (Franco Cortés & Roldán Vargas, 2015). This article is built by applying a basic assumption of the hermeneutic method with the aim of understanding, from the Comprehensive Health Care Policy promulgated by Resolution 429 of 2016, the reorientation of the objectives of the health system in the country.